Analysis of the consequences of fragmentations in low and geostationary orbits. Issue 8 (15th April 2016) - Rossi, A.; Lewis, H.; White, A.; Anselmo, L.; Pardini, C.; Krag, H.; Bastida Virgili, B.
Abstract: The present distribution of intact objects is a good proxy to quantify the catastrophic collision risk and consequences in the coming decades. The results of a large number of long term simulations of the LEO environment perturbed by the collisional fragmentation of massive objects are used to identify the main driving parameters of the long term collisional evolution of the debris population and measure the danger represented by "typical" classes of space objects. An evaluation norm, able to highlight the differences between comparative long term evolution scenarios and to give a quantitative measure of the effects of specific parameters affecting the evolution, is devised. It is shown how, for collisional fragmentations in LEO, due to the highly stochastic evolution of the LEO environment, even the fragmentation of a massive spacecraft might not be able to alter the long term evolution of the LEO population beyond the intrinsic statistical variability associated with the Monte Carlo procedure. Among the parameters determining the long term effects of a collisional fragmentation in LEO, a combination of mass and altitude of the event appears to be the driving factor. In GEO, the situation is different, and the addition of a massive fragmentation lives a signature on the environment that is detectable throughout the investigated time span, with the mass being the only factor important to asses the long term consequences of a collisional fragmentation.